Escaping superoscillations. (11th December 2017) - Berry, M V; Fishman, S
Abstract: A detailed classical model supports and elaborates an old prediction that in some circumstances gamma radiation could emerge from a box containing only red light. The 'red light', travelling nondispersively in a thin tube, is represented by a superoscillatory function: a band-limited function which in some regions oscillates faster than its fastest Fourier component. A weakly transmitting window opens and closes as the superoscillations pass by, releasing light into a half-plane. Detailed analysis of the spectrum of emerging light shows that the superoscillations escape, and propagate into the far field as 'gamma radiation', described precisely by a causal scattering amplitude.